SISTEM KONTROL DAN MONITORING SMART GARDEN HOUSE BERBASIS IOT MENGGUNAKAN ESP8266 SERI-01 DAN ARDUINO UNO - Pratama, Ilham; Pornomo, Bayu; Apriansyah, Arif (Jurnal Teknik Elektro, 2024)
The development of IOT-based technology is currently being favored by many people because of the convenience offered by this technology. Many things can be done with this technology as long as it is still connected to the internet. Of course this will be very helpful for example to control and monitor the condition of a room online and realtime, to do that it is necessary to make a tool that can control and monitor the condition of a smart garden room because if it is done in a room then the condition can be controlled and monitored. Smart Garden prototype design is a solution to take the right action during extreme weather and reduce human error. The Internet of Things (IoT)-based Smart Garden prototype uses the ESP8266 Series-01 as the User Interface in the monitoring system and uses the Soil Moisture sensor as input for soil moisture conditions. Soil moisture conditions where the results of the process are sent through an automatic watering smartphone. Based on the test results obtained a result that the tool can work correctly in accordance with what is instructed. The interface has also worked well where the data displayed is in accordance with the conditions received and the delivery delay is not too long around 1 second.